Chronic thromboembolic pulmonary hypertension: the diagnostic assessment - Simeone, Beatrice; Maggio, Enrico; Schirone, Leonardo; Rocco, Erica; Sarto, Gianmarco; Spadafora, Luigi; Bernardi, Marco; Ambrosio, Luca D’; Forte, Maurizio; Vecchio, Daniele; Valenti, Valentina; Sciarretta, Sebastiano; et al. (Frontiers in Cardiovascular Medicine, 2024)
Chronic Thromboembolic Pulmonary Hypertension (CTEPH) presents a significant diagnostic challenge due to its complex and often nonspecific clinical manifestations. This review outlines a comprehensive approach to the diagnostic assessment of CTEPH, emphasizing the importance of a high index of suspicion in patients with unexplained dyspnea or persistent symptoms post-acute pulmonary embolism. We discuss the pivotal role of multimodal imaging, including echocardiography, ventilation/perfusion scans, CT pulmonary angiography, and magnetic resonance imaging, in the identification and confirmation of CTEPH. Furthermore, the review highlights the essential function of right heart catheterization in validating the hemodynamic parameters indicative of CTEPH, establishing its definitive diagnosis. Advances in diagnostic technologies and the integration of a multidisciplinary approach are critical for the timely and accurate diagnosis of CTEPH, facilitating early therapeutic intervention and improving patient outcomes. This manuscript aims to equip clinicians with the knowledge and tools necessary for the efficient diagnostic workflow of CTEPH, promoting awareness and understanding of this potentially treatable cause of pulmonary hypertension.